2005
DOI: 10.1097/00007632-200501010-00015
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Joint Proprioception in Patients with Cervical Myelopathy

Abstract: Proprioceptive ability is impaired in patients with cervical myelopathy. Position sense can be assessed by measuring the angular error when reproducing criterion positions, and the results may reflect the severity of cervical myelopathy. Thus, the present method of measuring proprioception is easy to perform and useful for quantitative assessment of the severity of cervical myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Paradoxical embolism originating from the operative site and reaching the arterial circulation through a patent foramen ovale has rarely been reported as a cause of perioperative retinal vascular occlusion. [9] Hypotension per se seems to be a rare cause of retinal ischemia.…”
Section: Causes Of Vision Loss After Spine Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxical embolism originating from the operative site and reaching the arterial circulation through a patent foramen ovale has rarely been reported as a cause of perioperative retinal vascular occlusion. [9] Hypotension per se seems to be a rare cause of retinal ischemia.…”
Section: Causes Of Vision Loss After Spine Surgerymentioning
confidence: 99%
“…After surgery a patent foramen ovale was discovered and it was believed that he had sustained a paradoxical air, fat, or bone marrow embolization from the operative site in the lumbar spine. [9]…”
Section: Causes Of Vision Loss After Spine Surgerymentioning
confidence: 99%
“…Prolonged activation of BF may, for example, have produced the higher hip extensor moment and power generated at loading response to facilitate forward translation of the trunk over the supporting limb where the contra-lateral pre-swing phase has failed to generate adequate propulsion [21]. The prolonged activation of TA was not accompanied by co-activation with MG. Its isolated prolonged activation may have been a strategy to increase the stability of the ankle during stance due to impaired proprioception and joint position sense, previously identified in CSM [22].…”
Section: Discussionmentioning
confidence: 92%
“…8 It was also shown that proprioceptive loss recovered after surgery earlier than muscle strength. 9 The present results demonstrated that there was significant correlation between the scores of the hand function and the JOA scores, indicating there was a good association between the impairment of hand function and the extent of cervical myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently, it is reported that knee proprioception was impaired in cervical myelopathy and recovered after surgery. 8,9 Therefore, it is hypothesized that impairment of joint proprioception or light touch sensation may also affect the hand function of myelopathy patients. We measured the degree of proprioceptive impairment of the hand as well as that of light touch sensation loss, and assessed the association between hand function and proprioceptive impairment in patients with cervical myelopathy.…”
mentioning
confidence: 99%